2020
DOI: 10.4187/respcare.06877
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Critical Care Practitioners With a Decision Support Tool for Weaning Mechanical Ventilation in Children

Abstract: BACKGROUND: There is evidence that ventilator weaning protocols provide benefit to children receiving mechanical ventilation, but many protocols do not include explicit instructions for decreasing ventilator support from maximal settings. We evaluated care provider opinions on ventilator weaning recommendations made by a computerized decision support tool. METHODS: Recommendations for ventilator adjustment were generated using a computerized decision support tool based on the ARDSNet protocol using data from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the other hand, continuous titration of sedation might lead to a hesitancy in reducing sedatives after reaching a comfortable dosage and prolonging sedation, mechanical ventilation and length of stay ( 22 ). Likewise, it has been found that protocols for weaning from mechanical ventilation should include clear instructions for when to start reducing parameters in order to avoid unnecessary delay ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, continuous titration of sedation might lead to a hesitancy in reducing sedatives after reaching a comfortable dosage and prolonging sedation, mechanical ventilation and length of stay ( 22 ). Likewise, it has been found that protocols for weaning from mechanical ventilation should include clear instructions for when to start reducing parameters in order to avoid unnecessary delay ( 51 ).…”
Section: Resultsmentioning
confidence: 99%